What Matters When: A Multistage Model and Empirical Examination of Job Search Effort - Lopez-Kidwell, Virginie; Grosser, Travis J.; Dineen, Brian R.; Borgatti, Stephen P. (Academy of Management Journal, 2013)
We develop a multistage self-regulatory perspective on job search effort assuming active job seekers conducting job searches within a job search goal life span. Specifically, we propose that time pressure increases as the goal of finding employment becomes more proximal, while job search uncertainty decreases. Drawing on these premises, we integrate social comparison theory, control theory, and the attentional focus model of time pressure to hypothesize how various intrapersonal (i.e., prior effort, job search progress) and sociocontextual (i.e., effort put forth by peers in a social network) factors relate to job seekers' self-regulation of effort at different stages (i.e., preparatory, active-extensive, and active-intensive) of a job search process. In two studies of job seekers, we found that (1) prior job seeker effort is positively related to current effort across stages, (2) average peer job search effort is more strongly and positively related to job seeker effort earlier in job search, and (3) job search progress (i.e., the ratio of interviews to applications in Study 1 and perceived progress in Study 2) is negatively related to job seeker effort later in job search. Theoretical implications and future research directions are discussed.